2021
DOI: 10.3389/fmicb.2021.664386
|View full text |Cite
|
Sign up to set email alerts
|

Co-infections as Modulators of Disease Outcome: Minor Players or Major Players?

Abstract: Human host and pathogen interaction is dynamic in nature and often modulated by co-pathogens with a functional role in delineating the physiological outcome of infection. Co-infection may present either as a pre-existing pathogen which is accentuated by the introduction of a new pathogen or may appear in the form of new infection acquired secondarily due to a compromised immune system. Using diverse examples of co-infecting pathogens such as Human Immunodeficiency Virus, Mycobacterium tuberculosis and Hepatiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 130 publications
(144 reference statements)
0
37
0
2
Order By: Relevance
“…Also, it was reported that a fatal case of rapidly progressed extrapulmonary tuberculosis was triggered by COVID-19 infection in poor-adherence HIV-1-infected patient (CD4# 105/μL at COVID-19 diagnosis) [ 13 ]. Immuno-modulating effects of COVID-19 on pre-existing infectious diseases, such as tuberculosis, have been analyzed by biological models like 3D organoids [ 14 ]. Taken together, it is possible that unmasking of latent tuberculosis infection occurred owing to a cytokine storm with COVID-19 infection, although multiple replicates should be considered to conclude it.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was reported that a fatal case of rapidly progressed extrapulmonary tuberculosis was triggered by COVID-19 infection in poor-adherence HIV-1-infected patient (CD4# 105/μL at COVID-19 diagnosis) [ 13 ]. Immuno-modulating effects of COVID-19 on pre-existing infectious diseases, such as tuberculosis, have been analyzed by biological models like 3D organoids [ 14 ]. Taken together, it is possible that unmasking of latent tuberculosis infection occurred owing to a cytokine storm with COVID-19 infection, although multiple replicates should be considered to conclude it.…”
Section: Discussionmentioning
confidence: 99%
“…However, in almost all cases, such studies cannot represent the context and setting of pathogen infections in the real world. In particular, pathogens rarely exist in isolation but rather enter hosts already harbouring a diversity of pre-existing commensal or pathogenic organisms, each imposing their own effects on the within-host environment and immune system [1][2][3]. Furthermore, the community of organisms within a host may be unstable or destabilized by the new ingression.…”
Section: Introductionmentioning
confidence: 99%
“…Co-infection with pathogenic RNA viruses, including hepatitis C virus (HCV) and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), can affect disease severity and clinical outcomes ( Devi et al, 2021 ). There are limited data on the effects of HCV infection on outcomes in individuals with coronavirus disease 2019 (COVID-19), and no data on outcomes in individuals with long-term symptoms associated with COVID-19 (long COVID syndrome; post-acute sequelae of SARS CoV-2 infection [PASC]).…”
mentioning
confidence: 99%
“…Importantly, for HCV and SARS-CoV-2, the degree and nature of their interactions and the underlying mechanisms remain largely unexplored, although the potential for disease modulating effects of HCV infection on COVID-19 outcomes, including long COVID symptoms, is highlighted by evidence discussed in recent reviews ( Devi et al, 2021 ; da Mata et al, 2021 ). For example, one study suggests that among patients with HCV and hepatocellular carcinoma, those with undetectable HCV infection may be at a lower risk of fatality than those with active HCV infection, when diagnosed with SARS-CoV-2 infection ( Guler-Margaritis et al, 2021 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation